Acid-free copper foil adhesive tape, display module and mobile phone OLED screen

By setting an acid-free adhesive layer in the copper foil tape, reducing the acid value and combining the copper foil layer and release layer, the corrosion and bonding performance of the existing copper foil tape in high temperature and high humidity environments is solved, and the problem of insufficient corrosion and bonding performance of the existing copper foil tape in high temperature and high humidity environment is achieved. The excellent heat resistance and bonding properties of acid-free copper foil tape.

CN222226235UActive Publication Date: 2024-12-24SUZHOU DWELL NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420397302.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-01
Publication Date
2024-12-24
Estimated Expiration
2034-03-01

AI Technical Summary

Technical Problem

The polyacrylic adhesive used in existing copper foil tape is acidic, causing corrosion of the copper foil substrate, and has poor high temperature and high humidity resistance, which is easy to decompose in high temperature and high humidity environments, affecting the appearance and performance of the product.

Method used

Acid-free copper foil tape is used. By setting an acid-free adhesive layer, the acid value of the tape is reduced to 0 mg KOH/g, and the copper foil layer and the release layer are combined to improve the high temperature and humidity resistance and bonding properties of the tape.

Benefits of technology

It realizes excellent bonding performance and corrosion resistance of acid-free copper foil tape, avoids corrosion and discoloration problems, and meets application needs in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222226235U_ABST
    Figure CN222226235U_ABST
Patent Text Reader

Abstract

The utility model provides an acid-free type copper foil adhesive tape, a display module and a mobile phone OLED screen, the acid-free type copper foil adhesive tape comprises a copper foil layer, an acid-free adhesive layer and a release layer which are arranged in sequence, and by arranging the acid-free adhesive layer, the overall acid value of the adhesive tape can be reduced to 0 mg KOH / g, so that the obtained acid-free type copper foil adhesive tape not only has excellent adhesive property, but also can be used as an organic light-emitting diode display device. Meanwhile, the adhesive tape also has excellent heat and humidity resistance, and the problem that the existing acrylic copper foil adhesive tape is easy to corrode and discolor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of adhesive tapes, and in particular relates to an acid-free copper foil adhesive tape, a display module and a mobile phone OLED screen. Background Art

[0002] With the gradual promotion of OLED screens in electronic products such as mobile phones and computers, copper foil tape is also widely used in display modules (SCF modules). It mainly plays the role of thermal conductivity, heat dissipation and electromagnetic shielding, which can prevent the screen from overheating and resist electromagnetic wave interference.

[0003] At present, the main adhesive used for copper foil tape is polyacrylic acid. The colloid contains carboxyl and has a certain acidity, which will corrode the copper foil substrate, thereby causing the product to discolor and decay. In addition, the polyacrylic acid adhesive has poor resistance to high temperature and high humidity. It is easy to decompose in a high temperature and high humidity environment, resulting in more serious corrosion under high temperature and high humidity conditions or in the rainy season. At the same time, it will be accompanied by a pungent odor, which has a great impact on the appearance and performance of the product.

[0004] Therefore, in view of the above problems, developing an acid-free copper foil tape with excellent adhesion and high temperature and humidity resistance is a technical problem that is urgently needed to be solved in this field. Utility Model Content

[0005] In view of the shortcomings of the prior art, the purpose of the utility model is to provide an acid-free copper foil tape, a display module and a mobile phone OLED screen. By providing an acid-free adhesive layer, the acid value of the tape can be reduced to 0 mg KOH / g, so that the obtained acid-free copper foil tape not only has excellent bonding performance, but also has excellent moisture and heat resistance, thereby solving the problem that the existing acrylic copper foil tape is prone to corrosion and discoloration.

[0006] In order to achieve the purpose of this utility model, the utility model adopts the following technical solutions:

[0007] In a first aspect, the utility model provides an acid-free copper foil tape, wherein the acid-free copper foil tape comprises a copper foil layer, an acid-free adhesive layer and a release layer which are arranged in sequence.

[0008] The acid-free copper foil tape provided by the utility model comprises a copper foil layer, an acid-free adhesive layer and a release layer which are arranged in sequence. The acid-free adhesive layer is arranged as an adhesive layer, which not only has pressure sensitivity and can play a bonding role, but also can serve as a weather-resistant layer, thereby improving the high temperature and high humidity resistance of the entire acid-free copper foil tape, and can reduce the overall acid value of the acid-free copper foil tape to 0 mg KOH / g, thereby avoiding the problem that the existing acrylic copper foil tape is prone to corrosion and discoloration, so that the finally obtained acid-free copper foil tape has excellent high temperature and high humidity resistance, corrosion resistance and bonding performance, and meets the requirements for application in display modules.

[0009] It should be noted that the present invention does not impose any special restrictions on the preparation method of the acid-free copper foil tape provided.

[0010] It should also be noted that the materials of each layer in the acid-free copper foil tape provided by the utility model are existing materials, which can be directly purchased from the market, or can be purchased as raw materials and then prepared according to existing formulas.

[0011] As a preferred technical solution of the present invention, the thickness of the copper foil layer is 18 to 30 μm, for example, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm or 29 μm, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0012] As a preferred technical solution of the utility model, the copper foil layer is a rolled copper foil layer or an electrolytic copper foil layer.

[0013] As a preferred technical solution of the present invention, the thickness of the acid-free glue layer is 12 to 20 μm, for example, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0014] As the preferred technical solution of the utility model, the acid-free adhesive layer is an acid-free acrylic adhesive layer. The specific materials used include an acid-free acrylic copolymer and a curing agent. Conventional additives such as tackifying resins may also be added. The entire formula is an existing formula. For details, please refer to CN114149534A.

[0015] As a preferred technical solution of the present utility model, the release layer is a PET release layer.

[0016] As a preferred technical solution of the present invention, the thickness of the release layer is 25 to 50 μm, for example, 27 μm, 29 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm or 48 μm, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] As a preferred technical solution of the present invention, the thickness of the acid-free copper foil tape is 55 to 100 μm, for example, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm or 95 μm, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0018] In a second aspect, the utility model provides a display module, wherein the display module comprises the acid-free copper foil tape as described in the first aspect.

[0019] In a third aspect, the utility model provides a mobile phone OLED screen, wherein the mobile phone OLED screen comprises the display module as described in the second aspect.

[0020] Compared with the prior art, the utility model has the following beneficial effects:

[0021] The acid-free copper foil tape provided by the utility model comprises a copper foil layer, an acid-free adhesive layer and a release layer which are arranged in sequence. By arranging the acid-free adhesive layer, the overall acid value of the tape can be reduced to 0 mg KOH / g, so that the obtained acid-free copper foil tape not only has excellent bonding performance, but also has excellent moisture and heat resistance, thereby solving the problem that the existing acrylic copper foil tape is prone to corrosion and discoloration. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the cross-sectional structure of the acid-free copper foil tape provided by the utility model;

[0023] Among them, 1-copper foil layer, 2-acid-free adhesive layer and 3-release layer. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below by specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. The technical solution of the present invention is further described below by specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0025] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0026] In the description of the present invention, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0027] In a specific embodiment, the utility model provides an acid-free copper foil tape, the cross-sectional structure diagram of which is as follows: Figure 1 As shown, it includes a copper foil layer 1, an acid-free adhesive layer 2 and a release layer 3 arranged in sequence; wherein the acid-free adhesive layer 2 is pressure-sensitive, and the release layer 3 is torn off when in use, and can be directly used for bonding the display module;

[0028] In a preferred embodiment, the total thickness of the acid-free copper foil tape is 55 to 100 μm;

[0029] In another preferred embodiment, the copper foil layer 1 is a rolled copper foil layer or an electrolytic copper foil layer, and has a thickness of 18 to 30 μm;

[0030] In another preferred embodiment, the acid-free adhesive layer 2 is an acid-free acrylic adhesive layer with a thickness of 12 to 20 μm, and the material includes an acid-free acrylic ester copolymer and a curing agent. The amounts of the two can refer to the prior art, such as CN114149534A, wherein the acid-free acrylic ester copolymer and the curing agent can be selected from conventional commercial products;

[0031] In another preferred embodiment, the release layer 3 is a PET release layer with a thickness of 25 to 50 μm.

[0032] Example 1

[0033] An acid-free copper foil tape with a total thickness of 60 μm and a cross-sectional structure diagram as shown below: Figure 1 As shown, it includes a copper foil layer 1, an acid-free adhesive layer 2 and a release layer 3 arranged in sequence.

[0034] Wherein, the copper foil layer 1 is an electrolytic copper foil layer with a thickness of 18 μm;

[0035] The acid-free adhesive layer 2 is an acid-free acrylic adhesive layer with a thickness of 12 μm, and the raw materials include a 90:1 acid-free acrylic copolymer (purchased from DIC, model CT-6030) and an isocyanate curing agent (the formula refers to Example 1 of CN114149534A);

[0036] The release layer 3 is a PET release layer with a thickness of 30 μm.

[0037] Example 2

[0038] An acid-free copper foil tape with a total thickness of 100 μm and a cross-sectional structure diagram as shown below: Figure 1 As shown, it includes a copper foil layer 1, an acid-free adhesive layer 2 and a release layer 3 arranged in sequence.

[0039] Wherein, the copper foil layer 1 is a rolled copper foil layer with a thickness of 30 μm;

[0040] The acid-free adhesive layer 2 is an acid-free acrylic adhesive layer with a thickness of 20 μm, and the raw materials include a 90:1 acid-free acrylic copolymer (purchased from DIC, model CT-6030) and an isocyanate curing agent (the formula refers to Example 1 of CN114149534A);

[0041] The release layer 3 is a PET release layer with a thickness of 50 μm.

[0042] Example 3

[0043] An acid-free copper foil tape with a total thickness of 80 μm and a cross-sectional structure diagram as shown below: Figure 1 As shown, it includes a copper foil layer 1, an acid-free adhesive layer 2 and a release layer 3 arranged in sequence.

[0044] Wherein, the copper foil layer 1 is an electrolytic copper foil layer with a thickness of 20 μm;

[0045] The acid-free adhesive layer 2 is an acid-free acrylic adhesive layer with a thickness of 15 μm, and the raw materials include a 90:1 acid-free acrylic copolymer (purchased from DIC, model CT-6030) and an isocyanate curing agent (the formula refers to Example 1 of CN114149534A);

[0046] The release layer 3 is a PET release layer with a thickness of 45 μm.

[0047] Example 4

[0048] An acid-free copper foil tape is disclosed. The difference between the acid-free adhesive layer 2 and the embodiment 3 is that the thickness of the acid-free adhesive layer 2 is 10 μm, the total thickness of the acid-free copper foil tape is 75 μm, and the other structures and parameters are the same as those of the embodiment 3.

[0049] Comparative Example 1

[0050] An acrylic copper foil tape is disclosed, which differs from Example 3 in that an acrylic adhesive layer (the raw materials include a 90:1 polyacrylic acid adhesive (purchased from Yifeng, YF803) and an isocyanate curing agent) is used to replace the acid-free adhesive layer, and other structures and parameters are the same as those of Example 1.

[0051] Performance Testing:

[0052] (1) Peel strength at room temperature: Set the temperature to 23°C, attach a copper foil tape with a length × width of 25 mm × 140 mm to a steel plate, and perform a tensile test on a universal testing machine at a tensile speed of 300 mm / min. Take the average force of 40 to 140 mm.

[0053] (2) High-temperature peeling force: The temperature was set at 85°C, and a copper foil tape with a length × width of 25 mm × 140 mm was hot-pressed onto a steel plate. A tensile test was performed on a universal testing machine at a tensile speed of 300 mm / min, and the average force of 40 to 140 mm was taken.

[0054] (3) Acid value: Dissolve a certain amount of acid-free glue in a solvent, titrate it with a prepared KOH solution, and calculate the amount of KOH required for 1g of glue;

[0055] (4) High temperature and high humidity 3d appearance: Place the copper foil tape in an environment of 85°C and 85% humidity for 3 days and observe the color change of the appearance;

[0056] (5) High temperature and high humidity 3d peel strength: The copper foil tape was placed in an environment of 85°C and 85% humidity for 3 days, and then taken out to test its room temperature peel strength.

[0057] The acid-free copper foil tapes provided in Examples 1 to 4 and Comparative Example 1 were tested according to the above test method. The test results are shown in Table 1:

[0058] Table 1

[0059]

[0060] From the data in Table 1, we can see that:

[0061] The acid value of the acid-free copper foil tape provided in Examples 1 to 4 is 0 mg KOH / g, and the room temperature peeling force and high temperature peeling force are equivalent to those of the acrylic copper foil tape provided in Comparative Example 1. At the same time, after being treated in a high temperature and high humidity environment, the 3D appearance of the acid-free copper foil tape provided in Examples 1 to 4 does not show corrosion and discoloration, and the room temperature peeling force is slightly different from that before the high temperature and high humidity treatment, indicating that the acid-free copper foil tape provided in Examples 1 to 4 has both excellent bonding performance and high temperature and high humidity resistance;

[0062] The acid value of the acrylic copper foil tape provided in Comparative Example 1 is 31 mg KOH / g, and after being treated in a high temperature and high humidity environment, corrosion and discoloration appear on the appearance 3 days later, and the peeling force at room temperature is seriously reduced, indicating that the conventional acrylic copper foil tape provided in Comparative Example 1 has poor resistance to high temperature and high humidity.

[0063] The applicant declares that the utility model uses the above-mentioned embodiments to illustrate an acid-free copper foil tape, a display module and a mobile phone OLED screen, but the utility model is not limited to the above-mentioned embodiments, that is, it does not mean that the utility model must rely on the above-mentioned process steps to be implemented. The technicians in the relevant technical field should understand that any improvement to the utility model, the equivalent replacement of the raw materials selected by the utility model, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the utility model.

Claims

1. An acid-free copper foil tape, characterized in that: The acid-free copper foil tape comprises a copper foil layer, an acid-free adhesive layer and a release layer arranged in sequence; The acid-free adhesive layer is an acid-free acrylic adhesive layer.

2. The acid-free copper foil tape according to claim 1, characterized in that: The copper foil layer has a thickness of 18 to 30 μm.

3. The acid-free copper foil tape according to claim 1, characterized in that: The copper foil layer is a rolled copper foil layer or an electrolytic copper foil layer.

4. The acid-free copper foil tape according to claim 1, characterized in that: The thickness of the acid-free adhesive layer is 12 to 20 μm.

5. The acid-free copper foil tape according to claim 1, characterized in that: The release layer has a thickness of 25 to 50 μm.

6. The acid-free copper foil tape according to claim 1, characterized in that: The release layer is a PET release layer.

7. The acid-free copper foil tape according to claim 1, characterized in that: The total thickness of the acid-free copper foil tape is 55 to 100 μm.

8. A display module, characterized in that: The display module comprises the acid-free copper foil tape as claimed in any one of claims 1 to 7.

9. A mobile phone OLED screen, characterized in that: The mobile phone OLED screen includes the display module as described in claim 8.